Analysis of the vector hidden-charm tetraquark states without explicit P-waves via the QCD sum rules - Wang, Zhi-Gang (Nuclear physics. B, 2021)
In the present work, we adopt the scalar, pseudoscalar, vector, axialvector and tensor (anti)diquark operators as the elementary building blocks to construct vector and tensor local four-quark currents without introducing explicit P-waves, and explore the mass spectrum of the vector hidden-charm tetraquark states via the QCD sum rules comprehensively, and revisit the interpretations of the existing Y states in the scenario of vector tetraquark states. We resort to the energy scale formula to enhance the pole contributions and improve the convergent behaviors of the operator product expansion, and we should bear in mind that the predictions are rather sensitive to the particular energy scales which obey the uniform/same constraint. The predicted vector hidden-charm tetraquark states can be confronted to the experimental data in the future.